Integrated reporting and corporate performance in Nigeria: Evidence from the banking industry - A. E. Adegboyegun; M. E. Alade; A. O. Ademola; D. F. Eluyela; O. A. Oladipo (Cogent Business & Management, 2020)
The study examined the impact of integrated reporting on the performance of corporate organizations in Nigeria between 2009 and 2018. The major motivation for the study was the clarion call and the outcry by the public as regards environmental degradation due to firm activities. Unfortunately, such outcry were not really heard as information about the environment has not really been captured in the reports of firms which then makes them not accountable to their immediate environment. In the light of this necessity, the study which considered thirteen banks due to unavailability of data for the intended periods for the remaining five, used profit after tax as the dependent variable and also used IR index as a blend of financial and sustainability reporting, debt to equity ratio and total asset as independent variables. The study employed the classical Ordinary Least Square and Panel Co-integration techniques for analysis revealing that while IR has no significant impact on corporate performance in the short run, it has a significant relationship with firm performance in the long run. Hence, it was recommended that reporting authorities such as the FRCN should mandate firms to adopt the IR standard just like in South Africa as stipulated in their King's Code of Governance in a bid to strengthen such long run relationship. Also, non-financial information that embraces long-term forecasting should be included in corporate reports in a bid to educate relevant entities about its long-term prospects and its ability to continue in the foreseeable future.
Keywords: G21; G35; 650; corporate performance; information asymmetry; integrated reporting; nonfinancial information